The Relationship of Stress to Develop Alzheimer’s Disease: ความเครียดกับการเกิดโรคอัลไซเมอร์ - P, Ryden (Biomedical Sciences and Clinical Medicine, 2020)
The cause of Alzheimer’s disease still unclear; there is increasing evidence that chronic exposure to stress is a risk factor for Alzheimer’s and may also adversely affect the cause of the disease. Stress is becoming increasingly clear in neurodegenerative diseases, especially in the cognitive and memory areas of the brain where it can also disrupt neural circuits of stress responses. Disrupting these circuits produces abnormal emotional and aggressive behavior in patients. In addition, added stress drives the progression of the disease and can exacerbate symptoms. On the other hand, numerous prospective studies indicate that conditions associated with chronically elevated stress levels increase the risk of future dementia and Alzheimer’s disease. For instance, retrospective epidemiological studies provide robust evidence that a diagnosis of post-traumatic stress disorder is associated with an increased risk of dementia. This review, describes how neural and endocrine pathways activated by stress interact with ongoing Alzheimer’s disease and the relationship of stress and anxiety with Alzheimer’s. An increase in stress causes a more rapid development of pathology of the brain leads to Alzheimer’s disease.